Effect of topical ketanserin administration on intraocular pressure. Issue 6 (June 1993) - Costagliola, C; Iuliano, G; Rinaldi, M; Russo, V; Scibelli, G; Mastropasqua, L
Abstract : The effect of topical ketanserin on intraocular pressure (IOP) in normotensive and hypertensive eyes was evaluated. The study was performed on 10 healthy volunteers and 10 glaucomatous patients. Systolic arterial blood pressure (SBP), diastolic arterial blood pressure (DBP), heart rate (HR), IOP, tonographic outflow facility, pupil diameter, corneal thickness, and tear secretion were recorded at baseline and at 1 hour intervals for 12 hours after topical administration of 0.5% ketanserin or placebo, given in a randomised, double masked, crossover fashion. The alternative treatment was given 1 week later. In all subjects ketanserin significantly lowered IOP, while no variations in SBP, DBP, HR, pupil diameter, corneal thickness, and tear secretion were found. When subjects received placebo no significant variations of IOP occurred. Total outflow facility, measured by conventional tonography, increased significantly after drug administration in all subjects. Ketanserin is effective up to 6 hours in control subjects and 9 hours in glaucomatous patients. The placebo did not induce any change in this component of the aqueous humour dynamic in normal or in glaucomatous eyes. The findings indicate that topical ketanserin might be added to the list of antiglaucomatous agents.